Excavations at Kakrehta (Rupnath) - Sharma, R. K. 1932-; Mishra, Sudhakar N. (Agam Kala Prakashan, 1992)
On the archaeological excavations of the Kakrehta site in Jabalpur District, Madhya Pradesh.
Keywords: Kopertijd; Mesolithicum; Opgravingen; Ausgrabung; Copper age -- India; Excavations (Archaeology) -- India; Mesolithic period -- India; Indien; Kakrehta Site (India); Kakarehta